The Relationship between M&A Short Performance and Payment Method ----China Market in 2015 - Wang, Ranran (2016)
This thesis aim to examine the relationship between short term performance and payment method in M&A event. However, we just include pure equity and pure cash offers. It has other factors will affect the mixed offers’ performance except equity and cash. Firstly, we introduce some basic information about merger and acquisition. We define what are merger and acquisition and how to measure their performance. And then we introduce the methods of payment including equity and cash. We use event study method to find that there are extra returns through merger and acquisition. Besides, we use regress analysis find that the bidder’s size, TobinQ and payment method have positive impact on acquiring’s short term performance.